Distribution and characteristics of mineral inclusions in Hopea odorata Roxb. and Dryobalanops aromatic Geartn. f. - Toong, Wei Ching (2012)
This study was to investigate the occurrence, distribution, morphology, and dimension of mineral inclusions (calcium crystal and siliceous inclusion) in H. odorata and D. aromatica. Specifically, this study also attempted to compare the different amount of calcium crystals with regard to its growing and age of the tree. These species were selected due to deposition of mineral inclusion which leads to caused wearing in the woodworking cutting tools which contributed to processing economic. Siliceous inclusion deposited in D. aromatica has smooth and rough surface with globular, aggregate and irregular shape, and its size was ranging from 1.31 to 23.1 μm. Calcium crystal deposited was in druse form and that found to has sizes in ranging from 7.9 to 23.1 μm. The siliceous inclusion commonly deposited in wood ray and phloem ray, and even pith, but occasionally in axial parenchyma of wood and phloem. Pith area in the branch was lacking of mineral inclusions. The amount and size of siliceous inclusion was increased toward inner part of secondary xylem. The size was decreased, while the amount was increased with the tree height. At the pith this inclusion showed a decreased in the amount and size with an increased in tree height. Calcium crystal coexisted with siliceous inclusion in phloem ray and the cortex of the barks, and commonly found in separate cells. Mineral inclusions in the trunk bark were decreased in size with an increased in tree height, while in the root bark was decreased with an increasing in depth within the soil. Siliceous inclusion was deposited in epidermis while the crystal was deposited in palisade and spongy mesophyll of the leaf blade, and in cortex of the midrib and petiole, but occasionally in the parenchyma cell adjacent to vascular bundles of the petiole. Crystal found in leaf blade had smaller size than in petiole. H. odorata deposited the calcium crystal in form of druse and prismatic with four to eight planes, and with size ranging from 9.8 to 45.4 μm. Prismatic crystal was deposited in wood ray and the pith. The amount and the size of the crystals were increased toward inner part of secondary xylem, and decreased with an increasing in tree height. Druse crystal was commonly found in the phloem ray and the cortex, occasionally also found in wood ray and axial phloem parenchyma. The size was decreased in size with an increasing tree height. Crystals in young H. odorata’ s tree showed druse and prismatic form with four to ten planes in shape, and the size ranging from 7.4 to 53.3 μm. Both crystal forms were coexisting in wood ray, but druse crystal deposited in inflated ray cell or inflated chambered ray cell. Prismatic crystal was increased in size with an increasing tree height, while druse crystal size distribution was showed a reverse pattern. The crystal found in the pith was prismatic and showing decreasing size with an increased tree height. In the branch wood, the crystal was absent. Prismatic crystal was deposited in ray cells of root wood, but druse crystal was absent. The size of crystal in root wood was decreased as it goes deeper into soil. Druse crystals was deposited in spongy and palisade mesophyll of leaf blade, in the cortex of midrib and parenchyma and cortex of petiole in which size in petiole was larger than in leaf blade. Tree planted in Selangor which was older than tree planted in Perlis was showed fewer amount of crystals than in Perlis even in the young tree. The finding from this study, occurrence of mineral inclusions has a significant in the taxonomical characteristic and wood identification. The dimension and distribution pattern can serve as basis for investigation into wearing of woodworking cutting tools. It also filled the gap of knowledge of mineral inclusions in various tree parts.